Experimental investigation of the relationship between knowledge management and organizational innovation and creativity in the district 5 of Tehran municipality - Tavakoli, Mahsa (Archives of Business Research, 2016)
In the present research, effort is made to study the relationship between knowledge management and organizational innovation and creativity district 5 in the municipality of Tehran. This research has been implemented as a survey and the data and information is collected using a questionnaire. The statistical community, including all district 5 municipal staffs. Among different deputies of organization, using the method of multistage cluster sampling proportional to size, 90 individuals were chosen as samples.The findings of the present investigation have shown that, there is a significant relationship between all the components of knowledge management and organizational innovation. As well as the findings of regression analysis shows that the effect of knowledge management independent variable on the organizational innovation is significant and can be fitted to 2.7% of the dependent variable changes of the foregoing explication. The beta coefficient suggests that the pure effect of knowledge management variable on organizational innovation is (219.0) and is fitted for influencing positive also. This means that the increase in the rate of knowledge management results in the increase of organizational innovation and vice versa.